2013
DOI: 10.2147/ceor.s43662
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral treatment switch strategies for lowering the costs of antiretroviral therapy in subjects with suppressed HIV-1 viremia in Spain

Abstract: BackgroundThe current economic recession in European countries has forced governments to design emergency measures to reduce spending on drugs, including antiretroviral therapy (ART). Switching antiretroviral drugs for others that have the same efficacy and safety profile at a lower cost (cost-reduction measures, CRM) could prove to be a valid means of generating savings.MethodsDescriptive study of prospective consensus-based CRM undertaken in 2011 in a Catalonian hospital HIV unit among patients with prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
0
16
2
Order By: Relevance
“…At an international level, two articles proposed economic analysis of cost containment strategies in the field of HIV in Spain24 and in the UK 25. Llibre et al investigated the potential decrease in ART costs because of different therapy switch strategies within a hospital in Catalonia 24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At an international level, two articles proposed economic analysis of cost containment strategies in the field of HIV in Spain24 and in the UK 25. Llibre et al investigated the potential decrease in ART costs because of different therapy switch strategies within a hospital in Catalonia 24.…”
Section: Discussionmentioning
confidence: 99%
“…Llibre et al investigated the potential decrease in ART costs because of different therapy switch strategies within a hospital in Catalonia 24. The three main cost reduction strategies were switches to PI monotherapies, withdrawal of high cost molecules, and switch to less expensive backbones.…”
Section: Discussionmentioning
confidence: 99%
“…Cost analyses of the MONotherapy in Europe with TMC114 trial (MONET) trial showed a cost reduction of 52% with darunavir-ritonavir monotherapy compared to standard triple therapy [17]. Similarly, a 38% reduction in cost was shown in a Spanish observational cohort when switching from triple therapy to PI/r monotherapy [18]. These published data are in line with our deduction of potential costs savings in the United States based on the recommended monthly wholesale cost for commonly used regimens [14].…”
Section: Reductive Antiretroviral Therapy and Healthcare Policymentioning
confidence: 99%
“…In particular, the most relevant strategies were: (i) the rational use of diagnostic testing [5]; (ii) the implementation of health economics approach, in particular the definition of cost-effectiveness criteria [6], to compare the performance of different therapeutic alternatives, in addition to an economic forecast concerning the overall budget devoted to PLHIV treatment and care [7,8]; (iii) the use of protease inhibitor (PI) mono and dual therapies, the administration of Non-Nucleoside Reverse-Transcriptase Inhibitors (NNRTI)-based, instead of PI-based regimens, and the introduction of generic anti-retroviral drugs [5,6,7]. All these strategies could impact on the performances of the Hospitals Units and clinicians, taking in charge PLHIV and dealing with the problem of HIV, modifying the approach to the patients.…”
Section: Introductionmentioning
confidence: 99%